Implementation of Project-Based Learning to Enhance the Ecological Literacy of Students at Madrasah Ibtidaiyah Annizham, Jambi City - Dinda Reria Afrelin Hutabarat; M. Syahran Jailani; Ika Aryastuti Hasanah (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aimed to identify and determine the improvement of ecological literacy among these fifthgrade students through the implementation of the ProjectBased Learning (PjBL) model. The method used was Classroom Action Research (CAR) based on the Kemmis & McTaggart model, conducted over two cycles (two meetings each) in the Natural and Social Sciences (IPAS) subject. Data collection techniques included interviews, observations, questionnaires, and student worksheets (LKPD). The research subjects consisted of the IPAS teacher and 25 fifthgrade students of MI AnNizham Jambi City. The results showed an increase in students' ecological literacy across all aspects (Head, Heart, Spirit, & Hand). This was evidenced by the increase in the completion percentage of student worksheet scores, rising from 52% in Cycle I to 88% in Cycle II. Additionally, the completion percentage of student questionnaires also increased significantly from 20% in Cycle I to 84% in Cycle II. Based on these results, it can be concluded that the implementation of the ProjectBased Learning model is effective in improving students' ecological literacy.